PALAEOBIOLOGICAL OBSERVATIONS ON THE "COCOONED" MYTILID AMYGDALUM (BIVALVIA, UPPER PLIOCENE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Fossil specimens referred to the extant Atlantic-Mediterranean species Amygdalum politum (Verrill & Smith, 1880), occur in Upper Pliocene mudstones cropping out in northern Puglia (Southern Italy). Amygdalum is an infaunal mytilid living within a cocoon made of byssal threads, sediment and mucus. The examined material occurs in grey clayey silt, mainly massive, and in stratified yellowish clayey silt. The specimens from the grey mudstones are closed, strongly compressed, deformed and obliquely oriented. Also in the yellowish mudstones the shells are closed, compressed and intensely fractured but are concordant to the bedding plane and concentrated in a single pavement. On a whole, the associated macrofauna is indicative of upper slope tending to outer shelf environments. Taphonomic and palaeoecologic observations, together with the few available literature data, suggest that this bivalve lived in a particularly fluid substrate, keeping its vertical life position thanks to the stabilizing effect of the byssal cocoon. Since this species was able to cope with high turbidity waters, as suggested by taphonomic observation, it can be argued that the byssal cocoon acted also as a filter for the inhalant current.